“Hic Sunt Dracones”: Mapping the Rebellious Social Dynamics of Bel and the Snake from the Daniel and Joseph Competitive Court-tales - Porter, Christopher A. (Biblical theology bulletin, 2021)
Court tales provide narrative depictions of the imagined interface between the rulers of a society and their subjects and can often provide fuel for readings of self and society. Many of the canonical court tales display patterns of social interaction in new contexts (Egypt and Babylon) and assist in novel corporate contextualization. This article seeks to read the court tales of Bel and the Dragon (Daniel 14) in relationship to both the court tales of Aramaic Daniel (2–7) and the earlier tales of Joseph in Egypt (Genesis 41). It will then anchor these readings within the context of Alexandrian Egypt—one suggested location for composition—and see how they may suggest patterns of identity and social engagement for a plausible audience.